Introduction - Nicholls, Emily (Negotiating Femininities in the Neoliberal Night-Time Economy: Too Much of a Girl?, 2019)
‘Going out’ is widely recognised as a central leisure activity in the lives of many young people (Chatterton and Hollands, Urban nightscapes: Youth cultures, pleasure spaces and corporate power. Routledge, 2003; Waitt et al., ‘The guys in there just expect to be laid’: Embodied and gendered socio-spatial practices of a ‘night out’ in Wollongong, Australia. Gender, Place & Culture, 18(2), pp. 255–275, 2011), and engaging in leisure practices in the Night-Time Economy (NTE) is likely to be an important part of women’s lives in the UK. Indeed, the ‘night on the town’ is framed in many research accounts as offering important opportunities for young women to relax, socialise with friends and escape from the often mundane realities of everyday life, work and other responsibilities (Guise and Gill, ‘Binge drinking? It’s good, it’s harmless fun’: A discourse analysis of accounts of female undergraduate drinking in Scotland. Health Education Research, 22(6), pp. 895–906, 2007; Jayne et al., Emotional, embodied and affective geographies of alcohol, drinking and drunkenness. Transactions of the Institute of British Geographers, 35(4), pp. 540–554, 2010). Yet, young women’s experiences of the NTE are also clearly shaped by neoliberal and gendered expectations around consumption, body work and self-regulation. In particular, it is important to explore in more depth how—within a supposed ‘post-feminist’ context—expectations around ‘appropriately’ feminine dress and behaviour may continue to shape the experiences of young women like Nicole in contemporary leisure spaces. But what does it actually mean and look like for young women to be ‘feminine’ today? Is this something that is relevant or important to them? How are tensions around girliness and femininity lived and negotiated in practice in women’s everyday lives? And crucially, is it still more difficult for some women to adopt ‘appropriately’ feminine identities than others? This book considers these questions and explores the ways in which women’s participation in the UK NTE continues to be constrained in a supposedly post-feminist society (Harris, Jamming girl culture: Young women and consumer citizenship. In A. Harris (ed.) All about the girl: Culture, power and identity. Routledge, 2004).
Keywords: Contemporary Femininity; Contextual Expectations; Feminine Identity; Night-time Economy (NTE); Nightlife Scene